Effect of sodium citrate on lactose crystallization in concentrated whey. (2nd June 2020) - Pereira, João Pablo Fortes; Melquíades, Laís Lima; Stephani, Rodrigo; de Oliveira, Luiz Fernando Cappa; Perrone, Ítalo Tuler; de Carvalho, Antônio Fernandes
Abstract : Lactose crystallization, in concentrated whey, is considered a crucial step for drying efficiency as it impacts both production and spray dryer adhesion. The current study aimed to evaluate whether the addition of sodium citrate in concentrated whey may influence lactose crystallization during a simulated industrial condition. Based on the following results sodium citrate addition increases the final percentage of lactose crystallization in concentrated whey. Under practical conditions, dairy industries could add sodium citrate to the concentrated whey to improve lactose crystallization and powder stability (regarding stickiness and caking).